Diversity of Dragonflies (Odonata) Across Different Ecosystem Types on Karimun–Kemujan Island, Karimunjawa Archipelago - Alfiah Maula Salsa Billa; Fathurrahman sidiq; Jasmine Augi Nadifa; Salsabilla Khairunnisa; M. Ammar Ghirrid Muzakki (Universitas Negeri Semarang, 2026)
Dragonflies (Odonata) are members of the class Insecta that can be used as bioindicators to assess the quality of aquatic ecosystems. This study aims to evaluate the diversity of dragonfly species in the Karimunjawa area as an effort to assess the condition of aquatic ecosystems and their surrounding environments. Data collection was conducted in four habitat types: forest, rice fields, settlements, and mangroves. The method used was point count, with observations carried out in the morning from 08:00–11:00 WIB and from 15:00–17:00 WIB. The results showed that dragonfly diversity varied among habitat types, where the mangrove habitat had the highest species diversity (H’ = 2.23), while the settlement habitat showed the lowest richness (Dmg = 1.31). Several species recorded have the potential to serve as bioindicators of aquatic environmental quality in Karimunjawa. These findings indicate that the ecosystem conditions in the study area are still well preserved. However, further management and conservation efforts are required to ensure the sustainability of dragonfly habitats. This study provides one of the first habitat-based assessments of dragonfly diversity in Karimunjawa and contributes baseline information on species composition, habitat associations, and their potential use as bioindicators of aquatic ecosystem quality.